“Propagación sexual y clonal de sangre de grado (croton sp.) in vitro e invernadero en Tarapoto-Perú” - Lozano Del Águila, Jorge (2004)
The experiments were carried out in the facilities of the Plant tissue culture laboratory and greenhouse of the Faculty of Agrarian Sciences of the National University of San Martin, with the objectives of developing different strategies of sexual propagation and clonal in vitro and greenhouse and to describe sorne characteristic morphological of the small plants of "degree Blood" (Croton lechlen). lt was located in the University City, district of Morales, county and Region San Martin, Longitude West 76º 21 ', South Latitude 6º 29 ', Altitude, 350 m. s. n. m and Climate tropical dry forest (Holdridge 1972) .. In the sexual propagation for greenhouse the best results were, the treatment 3 with 87 .53% of germination of seeds and 5.09 cm of height; in the propagation in vitro the treatment 1with13.94 germinationo/o and 5.19% of formation of tripes. In the asexual propagation for explante of leaves and shafts, it formed bigger number of roots the treatment 2 with 20.00%. The brown color is a transition process in the physiologic aspect of the explante of leaves and petioles; the vitrificación is the brilliant state that it shows the fabric or the vitroplantas for excess of the water. In the asexual propagation of explante of leaves and petioles, the fenolización of the tripes has relationship with the death of the tripes in majority of the treatments. The treatments 1, 2 and 3 with 100% survival, morfogénesis and green color are the best results in the asexual propagation for explante of knots.